Ländliche Neusiedlung in Mitteleuropa vom Ende des 19. Jahrhunderts bis zur Gegenwart als nationalpolitisches Instrument: Ziele, zeitgenössische Stellungnahmen und Ergebnisse - Smit, Jan G. (ERDKUNDE, 1986)
The inner colonization in Central Europe during the last hundred years is now an historical phenomenon, which got its importance because of its significance as an instrument to strengthen the national state. The term inner colonization has been used in a different way in European countries. In those countries where only a small amount of the surface has been used for colonization, the erection of some farmhouses has been typified as colonization. In other countries with large scale activities only the construction of new villages or the planning of new rural landscapes has been interpreted as colonization. Different forms of colonization can be typified according to the kind of the land, the composition of the colonizing people and the structure of the new settlements. The colonization area may be newly created land like land reclamations or uncultivated land such as peat or heathlands. It can also appear on already cultivated land, as in the case of the settlement on large estates. Settlements existing at the time were reconstructed. Colonization forms according to the colonizing population can be divided into the existing groups, e.g. farmers, land workers, etc. or according to the regions the population came from. Also the new settlements may be different according to the design: not only closed villages, but also villages built up of scattered farms can be planned. What forms of colonization was chosen depend on the national aims in connection with the colonization activities. The state can be interested in a larger population number in some rural regions, e.g. border regions, colonization may be a part of social policy, in order to lessen social stratification, agricultural policy may be the leitmotiv in colonization, increasing agricultural production by creation of new farms. To realize colonization activities central authorities created special organisations which had the possibility of buying land, selecting settlers, etc. The extension function of those organisations was also important. They had to inform the future settlers and other people about the colonization activities. Inner colonization activities within Central Europe were of limited significance in terms of total amount of activities whereas its ideological significance was of greater importance.